2013
DOI: 10.5194/acp-13-1781-2013
|View full text |Cite
|
Sign up to set email alerts
|

Composition and evolution of volcanic aerosol from eruptions of Kasatochi, Sarychev and Eyjafjallajökull in 2008–2010 based on CARIBIC observations

Abstract: Large volcanic eruptions impact significantly on climate and lead to ozone depletion due to injection of particles and gases into the stratosphere where their residence times are long. In this the composition of volcanic aerosol is an important but inadequately studied factor. Samples of volcanically influenced aerosol were collected following the Kasatochi (Alaska), Sarychev (Russia) and also during the Eyjafjallajökull (Iceland) eruptions in the period 2008–2010. Sampling was conducted by the CARIBIC platfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 82 publications
(110 reference statements)
3
42
0
Order By: Relevance
“…Weigelt et al (2009) analysed several hundred cloud encounters in five geographic regions using IAGOS-CARIBIC data and showed that deep convective clouds in the tropics act as a particle source. Another important source for UTLS aerosols is volcanic eruptions (Andersson et al, 2013) with significant impacts on the radiation budget of the LS and on cirrus cloud coverage . Andersson et al (2013) also calculated the residence time (1/e) of SO 2 in two volcanic clouds to be about 45 d.…”
Section: Utls Aerosol Particle Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Weigelt et al (2009) analysed several hundred cloud encounters in five geographic regions using IAGOS-CARIBIC data and showed that deep convective clouds in the tropics act as a particle source. Another important source for UTLS aerosols is volcanic eruptions (Andersson et al, 2013) with significant impacts on the radiation budget of the LS and on cirrus cloud coverage . Andersson et al (2013) also calculated the residence time (1/e) of SO 2 in two volcanic clouds to be about 45 d.…”
Section: Utls Aerosol Particle Sourcesmentioning
confidence: 99%
“…Another important source for UTLS aerosols is volcanic eruptions (Andersson et al, 2013) with significant impacts on the radiation budget of the LS and on cirrus cloud coverage . Andersson et al (2013) also calculated the residence time (1/e) of SO 2 in two volcanic clouds to be about 45 d.…”
Section: Utls Aerosol Particle Sourcesmentioning
confidence: 99%
“…However, carbonaceous material was found in samples from the Kasatochi (Alaska, 2008), Sarychev (Russia, 2009) as well as Eyafjallajökull (Iceland, 2010) eruptions (Martinsson et al, 2009;Schmale et al, 2010;Andersson et al, 2013). The carbonaceous material most probably originates from air entrained into the volcanic cloud.…”
Section: Volcanic Emissionsmentioning
confidence: 99%
“…Jégou et al (2013) combined satellite-based limb and lidar measurements, ground-based lidar measurements and in situ balloon measurements to investigate Arctic region stratospheric aerosols from the Sarychev volcano eruption in the summer of 2009. Andersson et al (2013) investigated composition and evolution of volcanic aerosols from the eruptions of Kasatochi, Sarychev and Eyjafjallajökull in 2008-2010 based on CARIBIC (Civil Aircraft for Regular Investigation of the atmosphere Based on an Instrument Container) observations. Aerosol particles of 0.08-2 µm aerodynamic diameters were collected.…”
Section: Introductionmentioning
confidence: 99%